Seroprevalence of lymphocytic choriomeningitis virus in Nova Scotia - Marrie, TJ; Saron, MF (The American journal of tropical medicine and hygiene, 1998)
An ELISA system was used to determine the rate of seropositivity to lymphocytic choriomeningitis virus (LCMV) among a random sample of 505 Nova Scotians. Twenty (4%) were positive. Complete questionnaire data were available on all 20 seropositive subjects and on 449 seronegative subjects. Seventeen (85%) of the seropositive subjects were females (P = 0.03). It is concluded that infection with LCMV is present in Nova Scotia and females are more likely to be infected than males.